Simulated ice thickness, supraglacial debris thickness and subglacial topography for Khumbu Glacier, Nepal, using the iSOSIA ice-flow model - VERSION 2.0 - Rowan, Ann; Egholm, David (NERC EDS UK Polar Data Centre, 2021)
Simulated ice thickness (ice, metres, 100 m grid spacing) and supraglacial debris thickness (debris, metres, 100 m grid spacing) for Khumbu Glacier, Nepal, produced using the iSOSIA ice-flow model presented in Rowan et al. (2021; Journal of Geophysical Research-Earth Surface). The model domains used for the entire glacier and active glacier simulations (metres above sea level, 100 m grid spacing), and the present-day ice thickness estimate (metres, 30 m grid spacing) used to create the subglacial topography are included. The files contained in this collection present the outputs from three experiments carried out in Rowan et al. (2021; Journal of Geophysical Research-Earth Surface): 1. Simulation with a continuous debris layer, where h0 = 0.23 m and dT = 1.5 degC, showing the effect of change in mean annual air temperature to the present day (2015 CE) from 1.5 degC relative to the Little Ice Age 2. Simulation with a discontinuous debris layer, where h0 = 0.94 m and dT = 1.5 degC 3. Simulation with a discontinuous debris layer of the active glacier, where h0 = 0.94 m and dT = 1.5 degC The subglacial DEMs used for the model domains for the entire glacier and the active glacier, and the present-day (2015 CE) ice thickness estimated by Rowan et al. (2015, EPSL) to create the subglacial topography are also included (3 files). Funded by NERC under grant: NE/P00265X/1 "EverDrill: Accessing the interior and bed of a Himalayan debris-covered glacier to forecast future mass loss" to Duncan Quincey (PI) and Ann Rowan (CoI). : Model outputs were created using the iSOSIA ice-flow model version spm-3.3.3 to simulate the feedback between debris thickness, ice flow and mass balance. This model version is presented and described in detail in Rowan et al. (2015, Earth and Planetary Science Letters). The files contained in this collection present the outputs from three experiments carried out in Rowan et al. (2021; Journal of Geophysical Research-Earth Surface): 1. Simulation with a continuous debris layer, where h0 = 0.23 m and dT = 1.5 degC, showing the effect of change in mean annual air temperature to the present day (2015 CE) from 1.5 degC relative to the Little Ice Age 2. Simulation with a discontinuous debris layer, where h0 = 0.94 m and dT = 1.5 degC 3. Simulation with a discontinuous debris layer of the active glacier, where h0 = 0.94 m and dT = 1.5 degC The subglacial DEMs used for the model domains for the entire glacier and the active glacier, and the present-day (2015 CE) ice thickness estimated by Rowan et al. (2015, EPSL) to create the subglacial topography are also included (3 files). These results differ from those presented in Version 1 (GB/NERC/BAS/PDC/01435) in that here the h0 values were revised based on a maximum debris thickness of 2.0 m (compared to 4.0 m in v1) and the simulations of the active glacier extent were not part of v1. : iSOSIA ice-flow model version spm-3.3.3 : The glacier model outputs are transient conditions collected from simulations made over longer periods. The higher-order iSOSIA model (Egholm et al., 2011, Journal of Geophysical Research-Earth Surface) was implemented using a 100-m grid spacing and forced by elevation-dependent accumulation and ablation gradients, modified where supraglacial debris was simulated to give a reduction in sub-debris melt equivalent to that found for a positively-skewed distribution of debris thickness (h0 = 1.1 m). For further details of the mass balance scheme, see Rowan et al. (2021; Journal of Geophysical Research-Earth Surface).